2002
DOI: 10.1007/s00268-002-6217-8
|View full text |Cite
|
Sign up to set email alerts
|

Minilaparotomy approach to terminal ileal Crohn’s disease

Abstract: The feasibility and safety of a minilaparotomy approach to terminal ileal Crohn's disease have not been fully elucidated. The purpose of this study was to compare early outcomes utilizing this technique as an alternative to conventional approaches. Nine patients with terminal ileal Crohn's disease (but no complicating enteric fistulas) who underwent minilaparotomy between January 1998 and September 2000 were studied prospectively. The minilaparotomy approach entails a complete surgical procedure performed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Another approach is minilaparotomy and many surgeons use this in preference to a conventional long midline incision. Nakagoe et al 45 reported a series of nine patients with terminal ileal disease, who successfully underwent surgery using minilaparotomy. A minilaparotomy incision is usually less than 7 cm, which is certainly adequate for performing strictureplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is minilaparotomy and many surgeons use this in preference to a conventional long midline incision. Nakagoe et al 45 reported a series of nine patients with terminal ileal disease, who successfully underwent surgery using minilaparotomy. A minilaparotomy incision is usually less than 7 cm, which is certainly adequate for performing strictureplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of a small incision is the perceived reduction in postoperative pain relief and the subsequently more rapid return of bowel function and hence recovery [10]. Several studies that compared laparoscopic and minilaparotomies colectomies with traditional open procedures have indicated that the shorter recovery may be due to the shorter incision [4][5][6][7][8][9], although this is not always the case [10][11][12].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, it has been claimed that a transverse incision allows access equivalent to the midline incision through a smaller incision [2]. This is important, as evidence from laparoscopic and minilaparotomy studies has suggested that a smaller incision results in less postoperative pain and faster recovery [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%